PELAKSANAAN PENDIDIKAN AGAMA ISLAM MULTIKULTURAL DI RINTISAN SEKOLAH BERTARAF INTERNASIONAL SMAN 1 PAMEKASAN - Edi Susanto (Research Institute and Community Engagement of IAIN MADURA, 2011)
Complex in all dimension life, start from most abstraction up to most concretet represents the fact which is given, irreversible and cannot disobey. Still,- realized or without in realizing - He, that complext, times, rill trap human being at destructive behavior and becomes conflict root, so that it is important to be traced fully seriousness. This article try to describe execution of Islamic education being based on multi-cultural, as one of effort minimizing the conflict with entrance of Islamic education . Through the approach qualitative with deep observation and deep interview as instrument of the first data collection, the article representing this research summary finds that education of multicultural in SMAN 1 Pamekasan is still executed in integrativeadditive pattern and not yet entered for transformatif level